RESISTENSI TERHADAP PRAKTIK DOMINASI KEKUASAAN DALAM INSTITUSI PENDIDIKAN USIA DINI: STUD I KAsus SEKOLAH 'AIZIF AH' DI YoGYAKARTA - M. Ridhah Taqwa (Jurnal Kependudukan Indonesia, 2011)
Preparation of human resources through education institutions have an important meaning, but the process would be tarnished if the educational institutions to be the arena of power domination. In this context, resistance has the same meaning as important, if the goal is to eliminate the practice of the domination of power that affectthe performance of stakeholders in school. The focus of this study are push factor the rise of resistance to the dominant of the subordinate, the process and intensity of resistance from stakeholders and the implications of the practice of domination for the school image. The focus of this study include triggers the rise of resistance to the dominant of the subordinate party, the process and intensity of resistance from stakeholders and the implications for the practice of dominance on the performance of education providers. This paper is based on the results of studies using qualitative approaches. Data collection methods, especially participant observation for 3 years. School boards unwillingness to accommodate the democratization, transparency and accountability in the school, and they even justify the structural and direct violence that triggered the practice of resistance led by the committee. Resistance not only from the committee, but also from the teachers and some school officials who have resigned. Resistance is a long process that starts from the emergence of collective consciousness the subordinate until to claim a vote of no confidence. Implications of long resistance is large enough, ie, declining student and imaging, the presence of structural violence or directly and it not conducive to learning process. Although in post-resistance the management of education is not fully accountability and transparency, but the relationships among stakeholders more conducive and imaging was started to improve at this school. In the future monitoring and management of education that is democratic and transparent is more important to aplicate the vision developed enterprise education charity.Keyword: domination, resistance, democratization, human resources.